Penetration of Soybean Root Systems by Abscisic Acid Isomers - Markhart, Albert H. (1982)
The penetration of soybean (Glycine max L. cv. Ransom) root systems by exogenously applied isomers of abscisic acid was monitored by measuring the concentration of the chemical in the xylem exudate of root systems exposed to a three bar hydrostatic pressure difference. The cis-trans isomer penetrated more readily than the trans-trans isomer; however, up to 6 hours was needed to reach steady-state values. Exogenous abscisic acid also decreased volume flux through the root system and increased total carbon dioxide efflux from the vessel containing the root system.